Como afectan la formulación de preguntas de integración y el aprendizaje cooperativo en el rendimiento de los estudiantes de física en la unidad de campo eléctrico - Flores Nicolalde, Francisca (2011)
At present, students have several difficulties in learning science, which are being reflected in their poor performance. These difficulties are due to their low participation in the classroom where they take a passive role, independence to learn their subjects and the limited integration of knowledge. For this reason, we designed and implemented a teaching strategy through Integration Questions and Cooperative Learning on a sample of 202 students enrolled at a university in Ecuador, corresponding to a 2x2 factorial analysis. From the results obtained from the F ANOVA test with a 0.05 level of significance, it was concluded that students who were exposed to Integration Questions had better performance than those who were not exposed to them, and that the Cooperative Learning improved performance of students who worked cooperatively compared to those who worked individually.